SELF-IMPROVEMENT FOR PEOPLE WITH DISABILITIES: A COMMUNITY EMPOWERMENT ENDEAVOUR - Lusfina, Lusfina; Rosidi, Rosidi; Yanti, Fitri (Universitas Islam Negeri Raden Intan Lampung, 2024)
People with disabilities are those who have limitations in communicating with other individuals. Society’s negative view of people with disabilities still provides limitations, especially in terms of employment, so empowerment in improving the quality of their lives needs to be carried out. This research aims to provide an overview of empowerment for people with disabilities. This research is a literature review and this method is research that uses secondary data. Based data was obtained using the help of the Publish or Perish search tool with the keyword “Empowerment of People with Disabilities” on Google Scholar with a maximum number of results of 100 and 8 articles with high citations and only 6 articles will be taken. The research result concluded that empowerment of people with disabilities requires good cooperation from various parties, including the government, organizations of people with disabilities, families, the surrounding environment, and even the people with disabilities themselves. Things that can be done to improve the quality of education for people with disabilities are providing education, mentoring, training, social assistance, business capital, and empowerment.